Enantioselective Organocatalytic Synthesis of Bicyclic Resorcinols via an Intramolecular Friedel−Crafts‐Type 1, 4‐Addition: Access to Cannabidiol Analogues. Issue 16 (12th July 2021) - Bryant, Laura A.; Shankland, Kenneth; Straker, Hannah E.; Johnston, Callum D.; Lees, Nicholas R.; Cobb, Alexander J. A.
Abstract: The organocatalytic transformation of resorcinols is extremely rare. In this article, we report a highly enantioselective, organocatalytic intramolecular cyclization of these systems by a Friedel–Crafts‐type 1, 4‐addition using a Jørgensen‐Hayashi‐like organocatalyst with a large silyl protecting group, and show that heat improves reaction yield with virtually no detriment to enantioselectivity. A variety of bicyclic resorcinols were obtained with excellent enantioselectivities (up to 94%). To show the utility of these constructs, and as part of a wider project involving the synthesis of cannabinoid‐like compounds, the resorcinol formed was used to generate both 'normal' and 'abnormal' cannabidiol (CBD) derivatives which were shown to have anticonvulsant activity. Abstract :